KOMPETENSI APARATUR PADA PENATAAN ADMINISTRASI DI KELURAHAN WAWALI PASAN KECAMATAN RATAHAN KABUPATEN MINAHASA TENGGARA - RACO, MARCHEL; PANGKEY, MASJE; KOLONDAM, HELLY (JURNAL ADMINISTRASI PUBLIK, 2019)
The purpose of this study was to determine the apparatus competence in administrativestructuring in Wawali Pasan Village, Ratahan District, Southeast Minahasa Regency. Based on theresults of research that has been done by the author, it can be concluded as follows: Self Contept orattitude, values and self-image possessed by someone is very good. So that in resolving problems andcomplaints from the community the employees can do it well and without obstacles. This is becausethere is a good relationship that exists in the work environment or in the community Knowledge orinformation / knowledge possessed by village employees in the field of structuring and implementingvillage administration. In this case, village officials' understanding of the demands and needs of thecommunity regarding village administration structuring is also already good, especially for the processof structuring village administration itself. The standard operational procedures are well understoodwhere the process starts with community data collection carried out by the respective ward head andthen forwarded to the kelurahan office through the kelurahan secretary who is then submitted to thelurah head to obtain authorization and returned to the community according to their individual needs.Skills or the ability to carry out certain physical tasks (certain mental tasks) are also good enough. Thisis also justified by the community who believes that village officials have carried out their duties well.Although related to the efficiency of the completion of tasks and complaints from the community is stilllacking. But some more understand because they know that each task and job and complaints from thecommunity are diverse and have a difficulty level in solving it because it takes more time to solve this.Kata Kunci: Keywords: Apparatus Competence, Administrative Arrangement